Effects of oral milk extracellular vesicles on the gut microbiome and serum metabolome in mice. Issue 21 (14th October 2021) - Du, Chunmei; Quan, Suyu; Nan, Xuemei; Zhao, Yiguang; Shi, Fangquan; Luo, Qingyao; Xiong, Benhai
Abstract : Milk extracellular vesicles (EVs) are rich in abundant bioactive macromolecules, such as glycoconjugates, proteins, lipids and nucleic acids, and these vesicles might transmit signals to human consumers. Abstract : Milk extracellular vesicles (EVs) are rich in abundant bioactive macromolecules, such as glycoconjugates, proteins, lipids and nucleic acids, and these vesicles might transmit signals to human consumers. However, it remains to be determined whether milk EVs import new pathogens to humans or are beneficial for human health. Here, C57BL/6 female and male mice were randomly divided into 4 EV dose levels (0, 1.5 × 10 9 p g −1, 1.0 × 10 10 p g −1 and 1.5 × 10 10 p g −1 ). Based on the alterations in body weight, the control group (0 p g −1, PBS) and the middle treatment group (1.0 × 10 10 p g −1 ) were chosen for further analysis of the effects of EVs on the gut microbiota and blood metabolites in mice, by 16S rRNA gene sequencing and untargeted metabolomics, respectively. We found that milk EVs increased the abundance of "beneficial" microbes such as Akkermansia, Muribaculum and Turicibacter, while decreased the level of "harmful" bacteria Desulfovibrio . Serum metabolites showed that EVs mainly changed the lipid and amino acid metabolism, and especially increased several serum anti-inflammatory factors, which might be beneficial for inflammation and other metabolic diseases. The results of KEGG analysis suggested that the enriched pathways were the intestinal immune network for IgA production, retinol metabolism, and d -glutamine and d -glutamate metabolism. Taken together, the positive effect of milk EVs on serum nutrient metabolism without promoting "harmful" bacterial colonization in female and male mice may indicate that they are safe bioactive molecules, and some of the changes they induce may provide protection against certain diseases.